2022
DOI: 10.1111/prd.12430
|View full text |Cite
|
Sign up to set email alerts
|

Interconnection of periodontal disease and comorbidities: Evidence, mechanisms, and implications

Abstract: Periodontitis, a microbiome‐driven inflammatory disease of the tooth‐attachment apparatus, is epidemiologically linked with other disorders, including cardio‐metabolic, cognitive neurodegenerative and autoimmune diseases, respiratory infections, and certain cancers. These associations may, in part, be causal, as suggested by interventional studies showing that local treatment of periodontitis reduces systemic inflammation and surrogate markers of comorbid diseases. The potential cause‐and‐effect connection bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 66 publications
(112 reference statements)
1
99
0
Order By: Relevance
“…The infection of H. pylori is highly correlated with oral diseases ( Perez-Perez et al., 2004 ; Anand et al., 2006 ), and the shift of oral microbial community induced by H. pylori is one of the potent reasons for the oral diseases ( Martin and Solnick, 2014 ). Periodontitis, a common microbiome-driven inflammatory disease ( Hajishengallis, 2022 ), was highly related to H. pylori infection. P. gingivalis , as an established pathogenic agent of periodontitis ( Miller and Scott, 2021 ), had a positive correlation with H. pylori .…”
Section: Helicobacter Pylori and Oral Microbiomementioning
confidence: 99%
“…The infection of H. pylori is highly correlated with oral diseases ( Perez-Perez et al., 2004 ; Anand et al., 2006 ), and the shift of oral microbial community induced by H. pylori is one of the potent reasons for the oral diseases ( Martin and Solnick, 2014 ). Periodontitis, a common microbiome-driven inflammatory disease ( Hajishengallis, 2022 ), was highly related to H. pylori infection. P. gingivalis , as an established pathogenic agent of periodontitis ( Miller and Scott, 2021 ), had a positive correlation with H. pylori .…”
Section: Helicobacter Pylori and Oral Microbiomementioning
confidence: 99%
“…It is intriguing to note that the oral cavity function as the gateway for external microorganisms and those that inhabit the mouth and associated structures impact distant systems and organs such as the eye. As it is scientifically proven that many systemic diseases manifest in the oral cavity, it is also known that chronic inflammation originating from the oral cavity influence the pathogenesis of diseases at the systemic level [ 61 ]. Several latest studies have strongly suggested the existence of a gut-retinal axis, emphasizing the role of dysbiosis of gut microbiota in the inception and advancement of uveitis [ 62 ], AMD [ 63 ], and glaucoma [ 64 ].…”
Section: Oral Microbiomementioning
confidence: 99%
“…Globally, periodontitis prevalence is estimated to affect 20 to 50 percent adults [ 2 ]. Periodontitis is associated with multiple systemic diseases and metabolic disorders including obesity, cardiovascular disease, and diabetes, among others [ 3 ]. Apart from shared risk factors, systemic inflammatory burden arising from chronic periodontal infection is considered central to the risk increment for systemic diseases attributed to periodontal disease [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is associated with multiple systemic diseases and metabolic disorders including obesity, cardiovascular disease, and diabetes, among others [ 3 ]. Apart from shared risk factors, systemic inflammatory burden arising from chronic periodontal infection is considered central to the risk increment for systemic diseases attributed to periodontal disease [ 3 5 ]. Hypertensive disorders of pregnancy are highly prevalent and pose risk for maternal and neonatal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%